Quantifying Intra-Arterial Verapamil Response as a Diagnostic Tool for Reversible Cerebral Vasoconstriction Syndrome - Sequeiros, J.M.; Roa, J.A.; Sabotin, R.P.; Dandapat, S.; Ortega-Gutierrez, S.; Leira, E.C.; Derdeyn, C.P.; Bathla, G.; Hasan, D.M.; Samaniego, E.A. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: There is mounting evidence supporting the benefit of intra-arterial administration of vasodilators in diagnosing reversible cerebral vasoconstriction syndrome. We prospectively quantified the degree of luminal diameter dilation after intra-arterial administration of verapamil and its accuracy in diagnosing reversible cerebral vasoconstriction syndrome.MATERIALS AND METHODS: Patients suspected of having intracranial arteriopathy on noninvasive imaging and referred for digital subtraction angiography were enrolled in a prospective registry. Intra-arterial verapamil was administered in vascular territories with segmental irregularities. The caliber difference (Caliberpost − Caliberpre) and the proportion of caliber change ([(Caliberpost − Caliberpre)/Caliberpre] × 100%) were used to determine the response to verapamil. The diagnosis of reversible cerebral vasoconstriction syndrome was made on the basis of clinical and imaging features at a follow-up appointment, independent of the reversibility of verapamil. Receiver operating characteristic curve analysis was performed to determine the best threshold.RESULTS: Twenty-six patients were included, and 9 (34.6%) were diagnosed with reversible cerebral vasoconstriction syndrome. A total of 213 vascular segments were assessed on diagnostic angiography. Every patient with a final diagnosis of reversible cerebral vasoconstriction syndrome responded to intra-arterial verapamil. The maximal proportion of change (P < .001), mean proportion of change (P = .002), maximal caliber difference (P = .004), and mean caliber difference (P = .001) were statistically different between patients with reversible cerebral vasoconstriction syndrome and other vasculopathies. A maximal proportion of change ≥32% showed a sensitivity of 100% and a specificity of 88.2% to detect reversible cerebral vasoconstriction syndrome (area under the curve = 0.951). The Reversible Cerebral Vasoconstriction Syndrome-2 score of ≥5 points achieved a lower area under the curve (0.908), with a sensitivity of 77.8% and a specificity of 94.1%.CONCLUSIONS: Objective measurement of the change in the arterial calibers after intra-arterial verapamil is accurate in distinguishing reversible cerebral vasoconstriction syndrome from other vasculopathies. A proportion of change ≥32% has the best diagnostic performance.AUCarea under the curveCDcaliber differenceIAintra-arterialICADintracranial atherosclerotic diseaseDSAdigital subtraction angiographyPACNSprimary angiitis of the central nervous systemPCproportion of changeRCVSreversible cerebral vasoconstriction syndromeROCreceiver operating characteristicTCHthunderclap headache